IEA SHC Task 42 / ECES Annex 29 WG A1: Engineering and Processing of PCMs, TCMs and Sorption Materials. (June 2016) - Ristić, Alenka; Furbo, Simon; Moser, Christoph; Schranzhofer, Hermann; Lazaro, Ana; Delgado, Monica; Peñalosa, Conchita; Zalewski, Laurent; Diarce, Gonzalo; Alkan, Cemil; Gunasekara, Saman N.; Haussmann, Thomas; et al.
Abstract: An overview on the recent results on the engineering and characterization of sorption materials, PCMs and TCMs investigated in the working group WG A1 "Engineering and processing of TES materials" of IEA SHC Task 42 / ECES Annex 29 (Task 4229) entitled "Compact Thermal Energy Storage" is presented.